2020
DOI: 10.1007/s40843-020-1445-x
|View full text |Cite
|
Sign up to set email alerts
|

Enabling topical and long-term anti-radical properties for percutaneous coronary intervention-related complications by incorporating TEMPOL into electrospun nanofibers

Abstract: Scavenging reactive oxygen species (ROS) by antioxidants has been demonstrated as the most effective strategy for preventing percutaneous coronary intervention (PCI)-related complications. However, topical and long-term delivery of ROS antioxidants to a specific vascular tissue is proven to be a great challenge. Herein, an ROS scavenger of 4hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl (TEMPOL) is incorporated into electrospun nanofibers with a tunable loading amount to achieve its topical applicability and lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Nrf2 is one of the known regulators of cellular responses to oxidative stress that controls the amount of intracellular ROS that transcriptionally activates antioxidant and cytoprotective genes through binding to antioxidant response element (ARE) motifs [57][58][59]. It has been reported that basal levels of Nrf2-ARE activity affected intrinsic cellular radiosensitivity [60].…”
Section: Mechanisms Of the Enhancement Of Synergistic Tumor Therapymentioning
confidence: 99%
“…Nrf2 is one of the known regulators of cellular responses to oxidative stress that controls the amount of intracellular ROS that transcriptionally activates antioxidant and cytoprotective genes through binding to antioxidant response element (ARE) motifs [57][58][59]. It has been reported that basal levels of Nrf2-ARE activity affected intrinsic cellular radiosensitivity [60].…”
Section: Mechanisms Of the Enhancement Of Synergistic Tumor Therapymentioning
confidence: 99%